Cyclin-Dependent Kinase Regulatory Subunit 2 Indicated Poor Prognosis and Facilitated Aggressive Phenotype of Hepatocellular Carcinoma. (22nd October 2019) - Zhang, Jie; Song, Qianqian; Liu, Jinxia; Lu, Lina; Xu, Yuqing; Zheng, Wenjie
Abstract : Cyclin-dependent kinase regulatory subunit 2 (CKS2) is a member of the cell cycle-dependent protein kinase subunit family, which is implicated as an oncogene in various malignancies. However, the clinical significance, oncogenic functions, and related mechanisms of CKS2 in hepatocellular carcinoma (HCC) remain largely unclear. In the present study, expression features and prognostic value of CKS2 were evaluated in the bioinformatic databases and HCC tissues. The effects of CKS2 on the malignant phenotypes of HCC cells were explored in vitro . According to the analyses of three bioinformatic databases, mRNA levels of CKS2 were elevated in HCC tissues compared with the normal tissues. Immunohistochemical assays found that high CKS2 expression was closely associated with liver cirrhosis (P = 0.019 ), poor differentiation (P = 0.02 ), portal vein invasion (P < 0.001 ), TNM stage (P = 0.019 ), tumor metastasis (P = 0.008 ), and recurrence (P = 0.003 ). The multivariate regression analyses suggested that CKS2 was an independent prognostic factor for overall survival (HR = 2.088, P = 0.014 ) and disease-free survival (HR = 2.511, P = 0.002 ) of HCC patients. Moreover, the bioinformatic analyses indicated that CKS2 might be associated with the malignant phenotypes in HCC progression. In addition, in vitro assays showed that CKS2 expression was higher in HCC cell lines than in normal liver cells. Knockdown of CKS2 remarkably repressed the proliferation, colony formation (P = 0.0003 ), chemoresistance, migration (P = 0.0047 ), and invasion (P = 0.0012 ) of HCC cells. Taken together, overexpression of CKS2 was significantly correlated with poor prognosis of HCC patients and the malignant phenotypes of HCC cells, suggesting that it was a novel prognostic biomarker and potential target of HCC.